Wanita Magazines (1969–1980): National Narratives, Imageries of Modernity and Womanhood in Nation Building - Zainurul Rahman; Nasya Bafhen; Juliette Peers (Wacana Seni Journal of Arts Discourse, 2015)
In Malaysia, similar to other countries such as the USA, UK and Australia, popular women's magazines were established under the governance of the country's major newspaper corporations. The mass circulation women's magazine Wanita, was created in 1969. This paper explores how Wanita acted as catalyst in presenting women's voices in Malaysian society and how it presented notions of modernity, through an examination of selected Wanita magazine covers following the early years of Malaysian independence. This paper will also present recent scholarly findings from the first visual and social cultural investigation of Wanita magazine ever undertaken and offers a new perspective on narratives of citizenship, nationalism and feminism in Malaysia. Beginning with a look at the role of the media in shaping national identity, the state of media freedom in Malaysia, and the emergent stage of Malaysian archiving, it then justifies our use of Wanita magazine as a case study and presents our discussion on how the early editions of the magazine worked actively to promote positive ideas of the role of women in Malaysian society.